Fostering Deep Learning in Early Childhood Education Through Traditional Games: Joyful, Meaningful, and Mindful Learning - Eriani, Eva; Nanda Pratiwi; Mastuinda; Iwan Siswanto (JOYCED: Journal of Early Childhood Education, 2025)
This study addresses the lack of meaningful planning in early childhood education (ECE) activities, particularly in the integration of traditional games. Traditional games possess rich educational value that can enhance learning experiences by making them joyful, meaningful, and mindful collectively referred to as deep learning in the context of this research, unrelated to artificial intelligence. The study aimed to explore how traditional games can be systematically implemented to foster deep learning in young children. Conducted as classroom action research, the study involved 16 children aged 5–6 years in a kindergarten setting, selected through purposive sampling. The research was carried out over two cycles, with data collected through structured observation and analyzed using descriptive quantitative methods to calculate developmental achievement percentages in cognitive, emotional, and social aspects. Results showed an increase in deep learning indicators: joyful learning rose from 62.5% in Cycle 1 to 87.5% in Cycle 2, meaningful learning from 56.3% to 81.3%, and mindful learning from 50.0% to 78.1%. These findings indicate that traditional games, when intentionally integrated into lesson plans, can significantly contribute to holistic child development. The study concludes that achieving deep learning through traditional games requires consistent implementation, teacher commitment, and thoughtful planning aligned with children's developmental stages.